2012
DOI: 10.1177/0888406412451158
|View full text |Cite
|
Sign up to set email alerts
|

Using Multimedia Tools to Support Teacher Candidates’ Learning

Abstract: Content Acquisition Podcasts (CAPs), created using Mayer’s Cognitive Theory of Multimedia Learning, are a form of instructional technology that can deliver critical course content and be used by teacher educators to conserve limited face-to-face instructional time. In this study, the authors investigate whether the sequence of instruction for CAP exposure (preview or review) paired with textbook reading affected knowledge gains on topics related to students with disabilities. They randomly assign preservice te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
(61 reference statements)
2
14
0
Order By: Relevance
“…Data analysis revealed that most students reported satisfaction with the CAP intervention and case studies. This study mirrors previous experimental studies (Kennedy, Ely et al, 2012;Kennedy et al, 2011) with recommendation to use CAPs in teacher preparation. Most final case assignments revealed strong knowledge gained from case studies.…”
Section: Podcast Use To Prepare Teacherssupporting
confidence: 91%
See 3 more Smart Citations
“…Data analysis revealed that most students reported satisfaction with the CAP intervention and case studies. This study mirrors previous experimental studies (Kennedy, Ely et al, 2012;Kennedy et al, 2011) with recommendation to use CAPs in teacher preparation. Most final case assignments revealed strong knowledge gained from case studies.…”
Section: Podcast Use To Prepare Teacherssupporting
confidence: 91%
“…Empirical evidence on podcasts and enhanced podcasts has evolved within recent years (Kennedy, Driver, Pullen, Ely, & Cole, 2013;Kennedy, Ely et al, 2012;Kennedy, Hart, & Kellems, 2011;, though there is still much to learn with regard to use of podcasts to effectively teach new practices to preservice and inservice teachers. Traditional audio-only podcasts are widely used in education (Saeed, Yang, & Sinnappan, 2009), yet scant empirical evidence exists to support the use of audio-only podcasts to promote measurable learning outcomes during higher education or PD activities (Heilesen, 2010).…”
Section: Podcast Use To Prepare Teachersmentioning
confidence: 99%
See 2 more Smart Citations
“…For the intervention, the first author developed a series of brief video modules based on the instructional principles advocated by Gormley and Ruhl (2007), and the features of explicit instruction as identified by Rosenshine and Stephens (1986). Specifically, the following features were addressed in module development: Kennedy et al, 2013;Kennedy, Ely, et al, 2012;Kennedy, Hart, & Kellems, 2011;. Table 3 provides an overview of how these principles were applied in the development of the Reading Series modules.…”
Section: Intervention Measures and Materialsmentioning
confidence: 99%